The Coastal Zone: A Vision of Comparative Law: Trascendencia ambiental - Serrano Castro, Rodrigo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The present text is born within the framework of studies on the importance and impact of the coastal zone in human settlements, and its legal regulation from a comparative law perspective, Autonomous University of Baja California Sur, México. “The Coastal Zone: A View of comparative law”.